Geometrical preference of anchoring sites in the unicellular organism Stentor coeruleus - Syun Echigoya; Takuya Ohmura; Katsuhiko Sato; Toshiyuki Nakagaki; Yukinori Nishigami (Proceedings of the National Academy of Sciences, 2026)
Organisms often inhabit environments comprising complex structures across various scales. Animals rely on visual information from surrounding geometrical structures for navigation. Even at the microscale, various microsediments form complex structures in microbial habitats. The movement of microorganisms is passively affected by collisions and hydrodynamic interactions with surrounding structures. However, the influence of microenvironmental geometry on behavioral changes of unicellular organisms that lack visual perception remains unclear. Here, we developed geometrically structured chambers to investigate anchoring site preferences in the swimming ciliate Stentor coeruleus . Our experiments revealed that S. coeruleus preferentially anchored in narrow regions characterized by specific geometrical features, including corner angle, depth, and curvature at the corner end. Before anchoring, free-swimming S. coeruleus changed its behavior to move along the boundary wall of the chambers, accompanied by Ca 2+ -induced asymmetrical body deformation. To further investigate how S. coeruleus moves along the wall continuously, we conducted a hydrodynamic simulation and revealed that the asymmetric morphology causes asymmetric propulsive forces, explaining wall-following behavior through physical interactions with a wall. Thus, morphological change near a wall causes wall-following behavior, facilitating the identification of these narrow anchoring sites. Our findings indicate that environmental geometry drives behavioral transitions in S. coeruleus through simple biophysical processes, enabling spatial selection without visual cues. Overall, these results suggest that microgeometry plays a key role in shaping ecological niches for unicellular microorganisms.